The impact of structural and macroeconomic factors on regional productivity - Sabine D'Costa; Enrique Garcilazo; Joaquim Oliveira Martins (European Regional Science Association (ERSA), 2012)
We aim to understand the impact of nation-wide structural policies such as product market regulation and employment protection legislation and that of macroeconomic factors such as trade exposure, inflation and the level of government debt on the economic growth of regions in the OECD. In particular we seek to explore how the impact of these nation-wide factors might vary across regions depending on their productivity gap with the most productive region in their country. Our hypothesis is that regional productivity growth is positively related to the productivity growth of the leading region within the country and positively related to the productivity gap with the region that has the highest level of productivity in the country (in other words productivity growth increases with distance to the productivity frontier as lagging regions catch up). We use a policy-augmented growth model in which the effects of macroeconomic and structural policies are estimated in addition to the usual determinants of regional growth, physical and human capital and regional labour market density. Our methodology enables us to test simultaneously the catching-up effect, the influence of the productivity growth of the leading region, and the effect of nation-wide policies and how this might vary with distance to the frontier. We use panel data on 335 regions in 30 OECD countries defined at territorial level 2, taken from the OECD Regional Database, between 1996 and 2007. We first find that the growth of frontier regions in OECD countries has a positive effect on regional growth. Secondly, regional growth increases in the productivity gap with the frontier region within the country. Thirdly, we find that nation-wide factors do affect regional growth, and sometimes differentially according to the productivity gap with the frontier region, advocating in favour of place-based policy responses. We consistently identify a negative effect of product market regulation on regional growth, which is larger for lagging regions than for leading regions. The negative effect of regulation on economic indicators has been empirically demonstrated, however we show that this effect is more detrimental to lagging regions. Employment protection legislation and inflation have a negative impact on regional growth overall, while trade exposure and government debt have a positive effect on regional growth on average.
Keywords: R10; R11; 330; regional economic growth; structural policies; catching-up; lagging regions